2018
DOI: 10.1002/ddr.21420
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the antinociceptive and ulcerogenic activity of the tapentadol–diclofenac combination in rodents

Abstract: Preclinical Research & Development The objective of the present study was to evaluate the tapentadol-diclofenac combination in three dose-ratios in the mouse acetic acid-induced visceral pain and their ulcerogenic activity on the stomachal mucous. Dose-response curves were generated for tapentadol, diclofenac, and their combination in the acetic acid-induced writhing test in mice. Moreover, the stomachs of animals were surgically removal and gastrointestinal ulcerogenic action of the combination was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
4
7
0
Order By: Relevance
“…All these findings were confirmed using both isobolographic analysis and interaction index. Similar results have been observed when other NSAIDs and tapentadol were used in somatic and visceral animal pain models (Barreras‐Espinoza et al, ; Zapata‐Morales et al, , ) as well as when paracetamol has been used in combination with other opioid analgesics in the formalin and acetic acid assays in rodents (Fernández‐Dueñas, Poveda, Sánchez, & Ciruela, ; Janovsky and Krsiak, ; Miranda, Puig, Dursteler, Prieto, & Pinardi, ; Miranda, Noriega, & Prieto, ).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…All these findings were confirmed using both isobolographic analysis and interaction index. Similar results have been observed when other NSAIDs and tapentadol were used in somatic and visceral animal pain models (Barreras‐Espinoza et al, ; Zapata‐Morales et al, , ) as well as when paracetamol has been used in combination with other opioid analgesics in the formalin and acetic acid assays in rodents (Fernández‐Dueñas, Poveda, Sánchez, & Ciruela, ; Janovsky and Krsiak, ; Miranda, Puig, Dursteler, Prieto, & Pinardi, ; Miranda, Noriega, & Prieto, ).…”
Section: Discussionsupporting
confidence: 77%
“…It has been shown that the effect of a two‐analgesic combination depends on the proportions in which this combination is tested, obtaining synergistic effects, additives as well as antagonisms. This kind of studies using several proportions of an analgesic combination are essential, particularly when human clinical trials will be carried out, the information of animal models could be the only guide to define the experimental doses (Barreras‐Espinoza et al, ; Maves, Pechman, Meller, & Gebhart, ; Zapata‐Morales et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Co‐administration of NSAIDs—such as ketorolac, diclofenac, and acetaminophen—and tapentadol has previously been shown to produce synergistic analgesic effects and a better safety profile of the drugs combination when compared with each individual drug in some pain mouse models [12–15]. Thus, the purpose of this study was to evaluate the possible synergistic interaction between dexketoprofen and tapentadol in the writhing test in mice.…”
Section: Introductionmentioning
confidence: 99%